Intimate Partner Violence Predicting Outcomes in Specialized Mediation and Traditional Litigation - Huber Gifford, Holly (Journal of family violence, 2025)
PurposeWe investigated intimate partner violence (IPV) victimization level ever in the relationship, as reported by parents at baseline, as a predictor of outcomes within each of three different dispute resolution processes: traditional litigation (n = 67 cases), shuttle mediation (n = 49 cases), and videoconferencing mediation (n = 50 cases).MethodThe sample included court cases of separating or divorcing parents reporting high levels of IPV victimization. Parent and case level immediate and one-year follow-up outcomes were examined.ResultsWithin all three dispute resolution types, higher baseline IPV predicted higher levels of ongoing IPV and harassment at follow-up. Results within the traditional litigation group were mixed. Higher baseline IPV was related to parent reports of feeling less safe and more upset during the process, less positive perceptions of the process, less confidence that the other party would follow the resolution, and in the year following case resolution, greater likelihood of re-litigation. But higher mother reported baseline IPV was associated with greater likelihood of sole legal custody being granted to mothers, and higher father reported baseline IPV was associated with greater likelihood of joint legal custody and fewer parenting hours for mothers. Some results raise concerns about videoconferencing mediation (i.e., higher IPV was related to lower levels of party reported feelings of safety, longer time to resolution, and at follow-up, higher levels of concerning interparental relationships). Most results had small effect sizes.ConclusionsRecommendations for family law professionals to better serve separating parents reporting high IPV are suggested.